Social inequalities, health and health care delivery - Kronenfeld, Jennie J. (Amsterdam ; Boston : JAI, 2002)
Research on social inequalities has a very long tradition in sociological research, and discussion of the impact of social inequalities on health and health care delivery has long been one of the more important topics covered by medical sociologists. The research presented in this volume varies in its coverage and its approach to issues of social inequality in health and health care delivery. This volume includes both theoretical and quantitative papers, and deals with complex understandings of macro system issues, the impact of the patient and individual factors on health and health care and the impact of the provider and interaction between providers and patients. The first section focuses on macro system issues and includes both theoretical approaches to the topic and quantitative approaches. The second section includes articles with a greater focus on patient characteristics. These articles vary greatly in their coverage, with some focusing on the US as a whole, and others on specific sections of the US or subgroups within the population such as African American women or the elderly. The third section focuses on providers and issues of social inequality and health care delivery. These papers examine issues of gender, race and poverty as examples of sources of inequality in modern societies. In contrast to the second section these papers pay more attention to individual factors and the focus of the chapters is on aspects of health care providers. Research on providers of care is another long, important research tradition within medical sociology. Social Inequalities, Health and Health Care Delivery should be useful reading for medical sociologists and people working in other social science disciplines studying health-related issues. The volume also provides information for health services researchers, policy analysts and public health researchers.
Explaining health-related inequalities with a social capital model / James W. Grimm and Zachary W. Brewster -- Inequalities created in bio-medicine as the body business / Barbara Hanson -- Unforeseen policy effects on the safety net: medicaid, private hospital closures and the use of local VAMCs / Blair D Gifford, Larry M. Manheim and Diane Cowper -- A critical realist perspective on class relations and health inequalities / Graham Scambler, Paul Higgs and Ian Rees Jones -- Social inequalities, psychological well-being and health: longitudinal evidence from a U.S. national study / Nadine F. Marks and Heejeong Choi -- Health lifestyles and social class in the deep south / M. Christine Snead and William C. Cockerham -- Midlife health of African-American women: cumulative disadvantage as a predictor of early senescence / Yvonne J. Combs -- Consumer direction in home and community-based long-term care systems / Mary Signatur and Lisa Hollis-Sawyer -- Organizational supports for and barriers to part-time work arrangements for professionals: the case of radiology / Chloe E. Bird, Martha E. Lang, Benjamin Amick and Jocelyn Chertoff -- Race and evaluation of health care providers: theoretical and methodological issues / Jennifer Malat -- Poverty and health disparities: lessons and solutions for health care providers / Marlene Wilken and Beth Furlong -- Physician office access for the uninsured: an observational study / Maurice Penner, Susan Pennerm, Shauna Verkade and Jana Brooks.
Includes bibliographical references.
Description based on print version record.
Keywords: Medically uninsured persons -- Medical care; Health services accessibility; Social groups; Health systems & services; Medical -- Health Care Delivery; Social Science -- Sociology -- General